Tangibot: A tangible-mediated robot to support cognitive games for ageing people—A usability study - Garcia-Sanjuan, Fernando; Jaen, Javier; Nacher, Vicente (Pervasive and mobile computing, 2017)
The ever increasing elderly population requires a revision of technology to make it usable and meaningful for them. Most applications take into account their reduced physical and cognitive abilities in order to provide assistive services, but this paper focuses on building technology to improve these capacities through cognitive games. We present Tangibot, a tangible-mediated robot aimed at enabling more intuitive and appealing interactions. A usability study conducted on subjects at three different levels of cognitive impairment (none, mild, and severe) reveals that it is usable and engaging for users with no or mild cognitive impairment, and even though it is less usable for persons with severe impairment, it triggers positive emotional reactions among them, which makes it promising for their use in therapeutic activities.